1997
DOI: 10.1007/s004820050071
|View full text |Cite
|
Sign up to set email alerts
|

Pilotuntersuchung zur Wirkung von niedrigenergetischen, extrakorporalen Stoßwellen auf Muskelfunktionsstörungen bei spastischen Bewegungsstörungen von Kindern

Abstract: ESW is suitable for use as an additional instrument for physiotherapeutic treatment of infantile cerebral palsy. The effective action of ESW on disturbed peripheral muscles has been discussed in terms of positive pressure and tensile wave forces and/or forces acting by cavitation. The results obtained in this pilot investigation showed particular a decrease in muscle stiffness. A controlled investigation with gait analysis and psychological control is to be undertaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Only one study was a multiple sessions study [ 24 ], while the others were single session studies. All the studies but one [ 14 ] were placebo controlled. In all the 4 studies muscle hypertonia was evaluated clinically and muscle hypertonia was reduced for at least 3-4 weeks after the treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one study was a multiple sessions study [ 24 ], while the others were single session studies. All the studies but one [ 14 ] were placebo controlled. In all the 4 studies muscle hypertonia was evaluated clinically and muscle hypertonia was reduced for at least 3-4 weeks after the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The major limitation of the reviewed studies is represented by placebo treatment. Six studies were not placebo controlled [ 14 , 17 20 , 23 ]. In the remaining 6 studies, the placebo treatments were applied using the same instrumentations used for FSWT or RSWT, but without shock wave energy [ 13 , 15 , 24 ] or using a method to prevent the shock waves from reaching the target muscles [ 16 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, extracorporeal shock wave therapy (ESWT) has become an alternative in the treatment of spasticity (summarized in Supplemental Table 1). 20 37 A by product of extracorporeal shock wave lithotripsy, ESWT has emerged as a noninvasive management option for tendon and other pathologies of the musculoskeletal system, 38 with only a few unwanted side effects such as temporary skin redness and pain during treatment. Prior studies on tendinopathy showed that ESWT can be as or more effective than other forms of treatment such as eccentric exercise, traditional physiotherapy, steroid injections, and surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It is known, accordingly to Manganotti et al [5] and Lohse et al [6], that shock waves reduces the spasticity and after the application of ESWT the muscle remains stable. The movement execution appears when the muscle tonus begins to increase.…”
Section: Introductionmentioning
confidence: 95%